Delayed gadolinium-enhanced MRI of cartilage (dGEMRIC) and T2 mapping of talar osteochondral lesions: indicators of clinical outcomes - Rehnitz, Christoph; Kuni, Benita; Wünnemann, Felix; Chloridis, Dimitrios; Kauczor, Hans-Ulrich; Weber, Marc-André (Journal of magnetic resonance imaging, 2017)
Purpose To evaluate the utility of delayed gadolinium-enhanced magnetic resonance imaging of cartilage (dGEMRIC) and T2 mapping in evaluation of type II osteochondral lesions (OCLs) of the talus and define cutoff values for identifying patients with good/poor clinical outcomes. Materials and Methods 28 patients (mean age, 42.3 years) underwent T2 mapping and dGEMRIC at least 1.5 years (mean duration, 3.5 years) after microfracture (n = 12) or conservative (n = 16) treatment for type II OCL. Clinical outcomes were considered good with an American Orthopedic Foot and Ankle Society score ≥80. The T1/T2-values and indices of repair tissue (RT; cartilage above the OCL) were compared to those of the adjacent normal cartilage (NC) by region-of-interest analysis. The ability of the two methods to discriminate RT from NC was determined by area under the receiver operating characteristics curve (AUC) analysis. The Youden index was maximized for T1/T2 measures for identifying cutoff values indicative of good/poor clinical outcomes. Results Repair tissue exhibited lower dGEMRIC values (629.83 vs. 738.51 msec) and higher T2 values (62.07 vs. 40.69 msec) than NC (P < 0.001). T2 mapping exhibited greater AUC than dGEMRIC (0.88 vs. 0.69; P = 0.0398). All T1 measures exhibited higher maximized Youden indices than the corresponding T2 measures. The highest maximized Youden index for T1difference was observed at a cutoff value of 84 msec (sensitivity, 78%; specificity, 83%). Conclusion While T2 mapping is superior to dGEMRIC in discriminating RT, the latter better identifies good/poor clinical outcomes in patients with type II talar OCL. Level of Evidence: 2 Technical Efficacy: Stage 3 J. Magn. Reson. Imaging 2017;46:1601-1610.